2018 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations Summary. Issue 23 (4th December 2018) - Soar, Jasmeet; Donnino, Michael W.; Maconochie, Ian; Aickin, Richard; Atkins, Dianne L.; Andersen, Lars W.; Berg, Katherine M.; Bingham, Robert; Böttiger, Bernd W.; Callaway, Clifton W.; Couper, Keith; Couto, Thomaz Bittencourt; et al.
Abstract : The International Liaison Committee on Resuscitation has initiated a continuous review of new, peer-reviewed, published cardiopulmonary resuscitation science. This is the second annual summary of International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations that includes the most recent cardiopulmonary resuscitation science reviewed by the International Liaison Committee on Resuscitation. This summary addresses the role of antiarrhythmic drugs in adults and children and includes the Advanced Life Support Task Force and Pediatric Task Force consensus statements, which summarize the most recent published evidence and an assessment of the quality of the evidence based on Grading of Recommendations, Assessment, Development, and Evaluation criteria. The statements include consensus treatment recommendations approved by members of the relevant task forces. Insights into the deliberations of each task force are provided in the Values and Preferences and Task Force Insights sections. Finally, the task force members have listed the top knowledge gaps for further research.